Design of a Novel W-Sinker RF LDMOS - Xiangming Xu; Han Yu; Jingfeng Huang; Chun Wang; Wei Ji; Zhengliang Zhou; Ying Cai; Yong Wang; Pingliang Li; Peng-Fei Wang; David Wei Zhang (Advances in Condensed Matter Physics)
A novel RF LDMOS device structure and corresponding manufacturing process are presented in this paper. Deep trench W-sinker (tungsten sinker) is employed in this technology to replace the traditional heavily doped diffusion sinker which can shrink chip size of the LDMOS transistor by more than 30% and improve power density. Furthermore, the W-sinker structure reduces the parasitic resistance and inductance and improves thermal conductivity of the device as well. Combined with the adoption of the techniques, like grounded shield, step gate oxide, LDD optimization, and so forth, an advanced technology for RF LDMOS based on conventional 0.35 μm CMOS technology is well established. An F+A power amplifier product with frequency range of 1.8–2.1 GHz is developed for the application of 4G LTE base station and industry leading performance is achieved. The qualification results show that the device reliability and ruggedness can also meet requirement of the application.